Town Hall Meetings and the Death of Deliberation - Field, Jonathan Beecher (Book collections on Project MUSE., 2019)
Jonathan Beecher Field tracks the permutations of the town hall meeting from its original context as a form of democratic community governance in New England into a format for presidential debates and a staple of corporate governance. In its contemporary iteration, the town hall meeting models the aesthetic of the former but replaces actual democratic deliberation with a spectacle that involves no immediate electoral stakes or functions as a glorified press conference. Urgently, Field notes that though this evolution might be apparent, evidence suggests many US citizens don't care to differentiate.